ҚАРАҚАЛПАҚ ХАЛЫҚ ЕРТЕКЛЕРИ ТИЛИНДЕГИ ЕЛИКЛЕЎИШ КОМПОНЕНТЛИ ФРАЗЕОЛОГИЗМЛЕРДИҢ ФОНЕТИКА-ЛЕКСИКАЛЫҚ ӨЗГЕШЕЛИКЛЕРИ - Юсупова, Б.Т. (FAN va JAMIYAT, 2021)
The article deals with phraseologisms with a single imitation component in the Karakalpak language. Such idioms are analyzed in the basis of the language of Karakalpak folk tales. Their phonetic and lexical differences are revealed.